PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Zalif Zalif; Saiful Bahri; Deni Martin; Moh Lutfi (Kampus Akademik Publiser, 2025)
This research is motivated by the low critical thinking skills of students. The study aims to determine whether there is an influence of the problem based learning model on the critical thinking skills of fourth grade students of SDN Braji. The type of research used is quasi-experimental, the sampling of the study was carried out by random sampling. The instrument for data collection is a test in the form of an essay. This means that there is an influence of the Problem Based Learning model on students' critical thinking skills. This is proven that different treatments will get different results.